Hubungan Pengetahuan dan Sikap dengan Perilaku Pencegahan Covid-19 pada Siswa di SMPN 13 Pesawaran - Achmad Farich; Wahid Tri Wahyudi; Chelda Ernita (Malahayati Nursing Journal, 2021)
ABSTRACT : RELATIONSHIP OF KNOWLEDGE AND ATTITUDE WITH COVID-19 PREVENTION BEHAVIOR IN STUDENTS AT SMPN 13 PESAWARANIntroduction: Based on observations made on offline students (outside the network) it was found that there were students who did not understand, obey and apply health protocols at school. It was found (39.7%) of students did not comply with the health protocol outside the supervision of the teacher, such as not bringing a mask to school, not keeping the distance between friends, and still having students touching the face area.Objective: It is known how the relationship between knowledge and attitudes with Covid-19 prevention behavior in students at SMPN 13 Pesawaran.Methods: This research uses quantitative research with observational analytic methods, namely research that tries to understand the relationship between variables by analyzing the data that has been obtained. The research design used is a cross-sectional design to determine the relationship between knowledge and attitudes with COVID-19 prevention behavior in offline students at State Junior High School (SMP N) 13 Pesawaran.Results: Statistical test of knowledge using chi-square, obtained P-Value 0.000 so that P-Value (0.00.5) then there is a relationship with the value of Odds Ratio 9.8 attitude statistic test using chi-square, obtained P-Value 0.01 so P-Value (0.10.5) then there is a relationship with the value of Odds Ratio 8.Conclusions and suggestions: Students of SMPN 13 Pesawaran have less than optimal knowledge and attitudes accompanied by less than optimal behavior in preventing Covid-19. To further improve supervision of school residents so that they always comply with health protocols to break the transmission line of Covid-19. Keywords: Knowledge, Attitude, Covid-19 Prevention Behavior     INTISARI : HUBUNGAN PENGETAHUAN DAN SIKAP DENGAN PERILAKU PENCEGAHAN COVID-19 PADA SISWA DI SMPN 13 PESAWARANPendahuluan : Berdasarkan pengamatan yang dilakukan pada siswa luring (luar jaringan)ditemukan adanya siswa yang belum memahami, mematuhi dan menerapkan protokol kesehatan disekolah. Ditemukan (39,7%) siswa yang tidak mematuhi protokol kesehatan diluar pengawasan guru seperti tidak membawa masker saat kesekolah, tidak menjaga jarak antar teman dan masih adanya siswa yang menyentuh area wajah. Tujuan : Diketahui bagaimana hubungan pengetahuan dan sikap dengan perilaku pencegahan Covid-19 Pada Siswa Di SMPN 13 Pesawaran.Metode : Penelitian menggunakan jenis penelitian kuantitaif dengan metode analitik observasional, yaitu penelitian yang mencoba memahami hubungan antar variable dengan menganalisis data yang telah diperoleh. Desain penelitian yang digunakan yaitu desain cross-sectional untuk mengetahui hubungan antara pengetahuan dan sikap dengan perilaku pencegahan COVID-19 pada siswa yang luring di Sekolah Menengah Pertama Negeri (SMP N) 13 Pesawaran.Hasil : Uji statistik pengetahuan menggunakan chi-square, didapat P-Value 0.000 sehingga P-Value ɑ (0.00.5) maka terdapat hubungan dengan nilai Oods Ratio 9.8 uji statistik sikap menggunakan chi-square, didapat P-Value 0.01 sehingga P-Value ɑ (0.10.5) maka terdapat hubungan dengan nilai Oods Ratio 8.Kesimpulan dan saran : Siswa SMPN 13 Pesawaran memiliki pengetahuan dan sikap yang kurang optimal diiringi dengan perilaku yang kurang optimal dalam pencegahan Covid-19. Agar bisa lebih meningkatkan pengawasan pada warga sekolah agar selalu mematuhi protokol kesehatan agar dapat memutus tali penularan Covid-19. Kata Kunci: Pengetahuan, Sikap, Perilaku Pencegahan Covid-19